CONSTRUCTING OF THE SUN CONCENTRATOR AND INVESTIGATING HEATING FEATURES - Shakhobiddin, Fayziev; Temirov, Sohib (Journal of Global Research in Mathematical Archives(JGRMA), 2020)
This article deals with the experienced results of a paraboloid-type concentrator designed as a solar kitchen for personal use.